The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jmor.20170
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the sexually dimorphic tarsal glands and tegumental glands in gonyleptoid harvestmen (Opiliones, Laniatores)

Abstract: In at least four closely related families of the diverse harvestmen lineage Gonyleptoidea, males may possess sexually dimorphic tarsal glands in the swollen tarsomeres of the basitarsus and/or metatarsus of leg I. The first histological and ultrastructural examination of the sexually dimorphic tarsal glands in leg I focused only on Manaosbiidae. In this study, we examine the morphology and ultrastructure of the sexually dimorphic glands, and their associated glandular openings, found in the basitarsus and/or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A tubular hemocoelic vessel, hereafter referred to simply as a "vessel," runs along the midline of the ventral surface of the leg and contains the inferior depressor/flexor tendon ( Fig. 3A; see Proud and Felgenhauer, 2013, this volume). The inferior depressor/flexor tendon enters through the dorsal wall of the vessel within the metatarsus and continues to the insertion point on the pretarsus.…”
Section: General Internal Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…A tubular hemocoelic vessel, hereafter referred to simply as a "vessel," runs along the midline of the ventral surface of the leg and contains the inferior depressor/flexor tendon ( Fig. 3A; see Proud and Felgenhauer, 2013, this volume). The inferior depressor/flexor tendon enters through the dorsal wall of the vessel within the metatarsus and continues to the insertion point on the pretarsus.…”
Section: General Internal Anatomymentioning
confidence: 99%
“…The glandular units consist of a secretory cell, intercalary cell, and cuticular duct with an associated enveloping cell ( Fig. 3A; see Proud and Felgenhauer, 2013, this volume). inermipes) that has been cut with a razor blade showing the superior tarsal tendon in the hemocoelic space and the inferior tarsal tendon within the leg vessel.…”
Section: General Internal Anatomymentioning
confidence: 99%
“…Chemical communication has also been correlated to sex in Opiliones. Tegumental gland openings located on the tarsus of the first, fourth and occasionally third leg, or the femur of leg one, are present in males but not females ( Willemart et al, 2010 ; Proud & Felgenhauer, 2013 ; Da Silva Fernandes & Willemart, 2014 ). Males rub the glandular pores on surfaces, and control the flow of pheromones excreted ( Da Silva Fernandes & Willemart, 2014 ; Murayama & Willemart, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gnaspini and Rodrigues () surveyed the morphology of the external openings of the ozopores of over 30 species of laniatorean harvestmen, including three cosmetid species, and found that cosmetid harvestmen have rounded, “simplified” ozopores in anatomical positions different from other gonyleptoideans. Proud and Felgenhauer () examined sexual variation in the morphology and ultrastructure of the tarsal glands of four cosmetid species. Bennett and Townsend () described intraspecific variation in ovipositor morphology for the cosmetid harvestman Cynortula granulata .…”
Section: Introductionmentioning
confidence: 99%